Post-irradiation degradation of radio-oxidized natural rubber latex films induced by 60Co gamma rays. (May 2023) - Ren, Meng; Luo, Jiemin; Xu, Duigong; Guo, Yakun; Jing, Zekun; Zhang, Hongjun; Feng, Peng; Shuai, Maobing
Abstract: The present work involves the post-irradiation aging of radio-oxidized natural rubber latex (NRL) films irradiated by 60 Co gamma rays. The NRL films underwent the two consecutive processes: irradiation oxidation in air with a dose of 0.1 kGy h −1 (pre-irradiation phase) and radiolysis in argon with a dose of 10 kGy h −1 (post-irradiation phase). The changes of oxygen-containing groups in radio-oxidized NRL films were subsequently analyzed by FTIR (ATR method), XPS, and Raman spectroscopy. Analysis of the EPR spectra of free radicals and macroscope properties (including mechanical and thermodynamic properties) were also carried out. Pre-irradiation of NRL films in air resulted in the rapid formation of various carbonyl and unsaturated carbonyl products related to aliphatic esters, ketones, and carboxylic acids. These were followed by the decomposition of the oxygen-containing functional groups in the post-irradiation phase. In particular, the formation of an enol tautomer of a β-diketone functionality was observed. The increase and decrease of free radicals by EPR analysis were closely related to the crosslinking and degradation of the NRL network structures induced by irradiation. Further analysis indicated that the variations in macroscopic properties of NRL films were attributed to the secondary reactions of free radicals. Mechanistic routes for these irradiation aging processes are proposed and discussed. Graphical abstract: Radio-oxidation of the surface layer of NRL film and crosslinking and degradation of the internal three-dimensional network induced by irradiation. Image 1 Highlights: Post-irradiation degradation of radio-oxidation natural rubber latex films were investigated. Mechanism for post-irradiation degradation of irradiation oxidation natural rubber latex films was proposed. The internal and external structure changes of natural rubber latex films before and after irradiation were discussed. The relationship between the structural changes and macroscopic properties of NRL films was analyzed.